The prevalence of microbiological contamination in ready- to- eat food and factors affecting it in Melaka - Zaid K; Jamal HH (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Background : A cross sectional study was carried out to determine the prevalence of microbiological contamination in ready- to-eat food and factors affecting it in Melaka from February 2008 till May 2008 in collaboration with the Food Safety and Quality Unit and District Health Offices in Melaka Tengah, Alor Gajah and Jasin. Methods : A purposive sampling of 101 food premises was carried out and 202 ready- to-eat food samples were collected and analysed microbiologically using standard methods. A total of 202 food handlers were randomly selected for questionnaire interview while rectal and nasal swabs were taken from them to determine their healthy carrier status of pathogenic food bacteria. Results : Results showed that the overall prevalence of microbiological contamination in ready- to-eat food was 35.1%, while prevalence by type of food was 42.0% for main dishes and 9.8% for staple food. The majority of the contaminations were due to coliforms (14.9%), total plate counts (12.4%) and Staphylococcus aureus (3.5%). The mean score for food premise inspection was 77.21 ± 10.32 and the prevalence of healthy carrier status of pathogenic food bacteria among the food handlers was 15.8%. The level of food handling practices among food handlers was influenced by sex (p=0.012) and formal training on food handling courses (p=0.009). There was a significant negative correlation between age and level of food handling practices among the food handlers (r = -0.163; p = 0.02). Poor food handling practices (p=0.02) and poor hygiene status among the food handlers (p<0.01) were factors that influenced microbiological contamination of food samples. A logistic regression analysis showed that poor food handling practices (Odds ratio=3.50; 95% CI=1.35-9.06) and poor hygiene status among food handlers (Odds ratio=13.16; CI=3.65-47.44) were significantly associated with healthy carrier status of pathogenic food bacteria. Conclusion : Poor food handling practices and poor hygiene status among food handlers were factors that influenced microbiological contamination of ready-to-eat food as well as healthy carrier status of pathogenic food bacteria.